Responsiveness of Money Market Rates to Monetary Policy Committee Meetings (MPC) Communications - Usman, Aminu Yusuf; Idris, Mahmud Alhassan; Kabiru, Shehu (NIU Journal of Social Sciences; Vol 6 No 2 (2020): KIU Journal of Social Sciences, Vol. 6 No. 2, June 2020, 2020)
The Monetary Policy Committee (MPC) provides two sets of information to the financial market; it contains information on the policy decision, typically in the form of a change in cost of borrowing {monetary Policy Rate (MPR)} and level of liquidity in the market {Cash Reserve Requirement (CRR)}. The change in the both MPR and CRR affects other rates in the market because it represents a change in the cost of funds to the banks as well as liquidity in the economy respectively. The other set of information is that the committee communicates the future direction of monetary policy. These communications are likely to affect the market expectations, and therefore affect the interest rates. This study uses daily data for the period 2010-2019 to estimate the separate effects of monetary policy communication on money market rates, the study employed EGACH technique. It is found that the cost-of-money effect on the on money market rate is significant. So also, the effect of MPC communication on is found to be significant. This suggests that central bank communications is potentially a viable tool of monetary policy design and implementation in Nigeria. The study therefore suggests that the CBN should be proactive in designing an optimal communication strategy.  Keywords: Interest rates, Monetary policy rate, Liquidity ratio, EGACH